2016
DOI: 10.1037/apl0000087
|View full text |Cite
|
Sign up to set email alerts
|

Displaying fairness while delivering bad news: Testing the effectiveness of organizational bad news training in the layoff context.

Abstract: Although giving bad news at work is a stressful experience, managers are often underprepared for this challenging task. As a solution, we introduce organizational bad news training that integrates (a) principles of delivering bad news from the context of health care (i.e., bad news delivery component), and (b) principles of organizational justice theory (i.e., fairness component). We argue that both the formal and fair delivery of bad news at work can be enhanced with the help of training to mitigate distress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 58 publications
1
27
0
Order By: Relevance
“…Akintoye, McIntosh, and Fitzgerald (2000), Akintoye and Main (2007) and Jha and Iyer (2007) emphasise in their research that commitment is a key factor for the successful project delivery and some studies related to organisational justice suggest that distributive, procedural and interactional justice predict organizational commitment (Allen & Meyer, 1990;Jason A. Colquitt et al, 2001;Folger & Konovsky, 1989). The same is applicable for conflict management which is an antecedent to project performance (Chan et al, 2004) and it has been suggested in prior research that organisational justice can be useful in difficult conversation or in delivering bad news (Lavelle, Folger, & Manegold, 2016;Richter, König, Koppermann, & Schilling, 2016).…”
Section: H1mentioning
confidence: 98%
“…Akintoye, McIntosh, and Fitzgerald (2000), Akintoye and Main (2007) and Jha and Iyer (2007) emphasise in their research that commitment is a key factor for the successful project delivery and some studies related to organisational justice suggest that distributive, procedural and interactional justice predict organizational commitment (Allen & Meyer, 1990;Jason A. Colquitt et al, 2001;Folger & Konovsky, 1989). The same is applicable for conflict management which is an antecedent to project performance (Chan et al, 2004) and it has been suggested in prior research that organisational justice can be useful in difficult conversation or in delivering bad news (Lavelle, Folger, & Manegold, 2016;Richter, König, Koppermann, & Schilling, 2016).…”
Section: H1mentioning
confidence: 98%
“…Organizations and managers therefore need to be aware of the interpersonal and moral challenges of implementing layoffs routinely both for layoff victims and layoff agents. In line with this, recent research has demonstrated that managers can be trained to deliver the bad news of a layoff in a professional and fair way (Richter, König, Koppermann, & Schilling, ).…”
Section: Discussionmentioning
confidence: 86%
“…Business leaders and practitioners can use this restructured method to improve the quality of ratings. Furthermore, the same basic method (i.e., having trainees emulate a role model rather than modify their own behavior based on a trainer's feedback) of restructured FOR training can also be applied to other types of training, such as teamwork skills (Hughes et al, ), news delivery (Richter, König, Koppermann, & Schilling, ), managerial decision‐making (Goodman & Wood, ), and principles regarding effective and ineffective teamwork (Smith‐Jentsch, Campbell, Milanovich, & Reynolds, ).…”
Section: Discussionmentioning
confidence: 99%